Transcriptomic data reveals MYC as an upstream regulator in laying hen follicular recruitment - Ashley E Kramer; Kathryn M Ellwood; Nicole Guarino; Cong-Jun Li; Aditya Dutta (Poultry Science)
Understanding the mechanisms of follicular recruitment is essential for improving laying hen and broiler breeder productivity, as it directly influences egg production. Despite advancements in poultry breeding for enhanced egg production, the factors driving successful ovarian follicle maturation remain inadequately understood. This study investigates the genetic drivers mediating the transition of pre-recruitment follicles to the pre-ovulatory phase, a crucial stage before ovulation. Using RNA sequencing and bioinformatics approaches such as a differential gene expression analysis, we compared pre-recruitment follicles with the recently recruited F5 pre-ovulatory follicle to identify key genes and upstream regulators involved in this transition. Further validation through qRT-PCR confirmed these findings. Using Qiagen's Ingenuity Pathway Analysis we identified MYC proto-oncogene (C-Myc) as a pivotal upstream regulator, controlling genes essential for cell proliferation and differentiation. Additionally, TGFβ1 emerged as a key regulator, influencing pathways involving SMAD3, TNF, and TP53. The study highlights the intricate regulatory network involving MYC and other transcription factors such as CTNNB1, crucial for follicular development. These findings provide valuable insights into the molecular mechanisms governing follicular selection and maturation, which are essential for enhancing egg production efficiency. Future research should explore the roles of MYC, CTNNB1, and other driver genes in follicular development to further understand and improve reproductive efficiency in poultry.